Palm Kernel Cake Fermented with Lentinus edodes in the Diet of Quail - Nuraini , Nuraini; Djulardi, Ade; Trisna, Ade (International Journal of Poultry Science, 2019)
Background and Objective: Palm kernel cake (PKC) represents an available alternative poultry feed component, fermentation of PKC by Lentinus edodes (L. edodes), a lignocellulolytic fungus (that produces ligninase and cellulase enzymes), increases the nutrient content and the quality of PKC. The present study was conducted to evaluate the effect of the incorporation of PKC fermented with L. edodes (PKCF) in quail diets on the production performance and egg quality. Materials and Methods: The present study used a completely randomized design (CRD) with five dietary treatment groups (0, 10, 15, 20 and 25% PKCF) and four replicates per treatment (10 quails per replicate). Two hundred and seven-week-old quails were included in the study. Diets were iso nitrogenous (20% crude protein) and iso caloric (2800 kcal kg–1). The measured parameters included feed consumption, hen -day egg production, egg weight, egg mass production and feed conversion and egg cholesterol content. Results: Addition of dietary PKCF up to 25% resulted in good feed consumption, hen-day egg production, egg weight, egg mass and feed conversion and the addition of PKCF decreased (p<0.01) egg cholesterol content. Conclusion: It is concluded that up to 25% PKCF in the diet resulted in good egg production performance while reducing the cholesterol content of the quail egg, indicating that this feed supplement should be considered for industrial use.